Recent Advances of Transition Metal Dichalcogenides‐Based Materials for Energy Storage Devices, in View of Monovalent to Divalent Ions - Ali, Salamat; Ahmad Shah, Syed Shoaib; Sufyan Javed, Muhammad; Najam, Tayyaba; Parkash, Anand; Khan, Shaukat; Bajaber, Majed A.; Eldin, Sayed M. M.; Tayeb, Roaa A.; Rahman, Mohammed M.; Qi, Jing (Chemical record, 2024)
The fast growth of electrochemical energy storage (EES) systems necessitates using innovative, high‐performance electrode materials. Among the various EES devices, rechargeable batteries (RBs) with potential features like high energy density and extensive lifetime are well suited to meet rapidly increasing energy demands. Layered transition metal dichalcogenides (TMDs), typical two dimensional (2D) nanomaterial, are considered auspicious materials for RBs because of their layered structures and large specific surface areas (SSA) that benefit quick ion transportation. This review summarizes and highlights recent advances in TMDs with improved performance for various RBs. Through novel engineering and functionalization used for high‐performance RBs, we briefly discuss the properties, characterizations, and electrochemistry phenomena of TMDs. We summarised that engineering with multiple techniques, like nanocomposites used for TMDs receives special attention. In conclusion, the recent issues and promising upcoming research openings for developing TMDs‐based electrodes for RBs are discussed. In this review work, 2D TMDs‐based materials and their physical, chemical, morphological, and electrochemical properties and challenges are discussed for RBs. 2D TMDs‐based cathode, anode, and electrolyte materials for RBs comprehensively studied and compared with their recent development. In conclusion, the progress and strategies to improve the performance of 2D TMDs for RBs are discussed.